Images of justice and curricular conceptions of law courses: A comparative analysis between images - Lorea Leite, Maria Cecília; Ferreira da Cunha, Natália; Pacheco Brum, Lucas (Revista Pedagogía Universitaria y Didáctica del Derecho, 2023)
This work aims to analyze, discuss, and identify similarities and differences between two images created by professors of the Law course at the Federal University of Rio Grande do Sul, in Brazil, and their reflections on the curricular conceptions of the courses. This article presents, in its first part, the methodological aspects that underlie and support the comparative analyses of our research, using the documentary method of interpretation, to analyze the images that make up this study, problematizing concepts such as access to justice, social justice, and social inequality. Finally, we address aspects that focus on the curriculum and, in the final considerations, we highlight what emerges from the comparison between the images, especially about curricular perspectives.